Impact of High Methane Flux on the Properties of Pore Fluid and Methane-Derived Authigenic Carbonate in the ARAON Mounds, Chukchi Sea - Kim, Ji-Hoon; Park, Myong-Ho; Lee, Dong-Hun; Minami, Hirotsugu; Jin, Young-Keun; Hachikubo, Akihiro; Hur, Jin; Ryu, Jong-Sik; Kang, Moo-Hee; Jang, Kwangchul; Kida, Masato; Seo, Yongwon; et al. (Frontiers in Marine Science, 2022)
We investigated the pore fluid and methane-derived authigenic carbonate (MDAC) chemistry from the ARAON Mounds in the Chukchi Sea to reveal how methane (CH4) seepage impacts their compositional and isotopic properties. During the ARA07C and ARA09C Expeditions, many in situ gas hydrates (GHs) and MDACs were found near the seafloor. The fluid chemistry has been considerably modified in association with the high CH4 flux and its related byproducts (GHs and MDACs). Compared to Site ARA09C-St 08 (reference site), which displays a linear SO42- downcore profile, the other sites (e.g., ARA07C-St 13, ARA07C-St 14, ARA09C-St 04, ARA09C-St 07, and ARA09C-St 12) that are found byproducts exhibit concave-up and/or kink type SO42- profiles. The physical properties and fluid pathways in sediment columns have been altered by these byproducts, which prevents the steady state condition of the dissolved species through them. Consequently, chemical zones are separated between bearing and non-bearing byproducts intervals under non-steady state condition from the seafloor to the sulfate-methane transition (SMT). GH dissociation also significantly impacts pore fluid properties (e.g., low Cl-, enriched δD and δ18O). The upward CH4 with depleted δ13C from the thermogenic origin affects the chemical signatures of MDACs. The enriched δ18O fluid from GH dissociation also influences the properties of MDACs. Thus, in the ARAON Mounds, the chemistry of the fluid and MDAC has significantly changed, most likely responding to the CH4 flux and GH dissociation through geological time. Overall, our findings will improve the understanding and prediction of the pore fluid and MDAC chemistry in the Arctic Ocean related to CH4 seepage by global climate change.